2013
DOI: 10.1097/dcr.0b013e31828b282c
|View full text |Cite
|
Sign up to set email alerts
|

Topical Glyceryl Trinitrate Ointment for Pain Related to Anal Hypertonia After Stapled Hemorrhoidopexy

Abstract: Topical 0.4% glyceryl trinitrate is effective in relieving pain and reducing anal resting pressure in patients with anal hypertonia after stapled hemorrhoidopexy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
(36 reference statements)
1
21
1
Order By: Relevance
“…Our normal range of the MRP is 40À80 mmHg and, although a preoperative MRP of over 80 mmHg appeared to be related to more pain in the present study (P = 0.058), it was not an independent predictor of postoperative pain. This is supported by a recent study of SH [25] in which only 33.9% (41/121) of patients with postoperative severe pain (VAS > 3) had an increased anal resting pressure. It therefore seems that anal sphincter spasm is unlikely to be a frequent cause of severe pain after SH.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our normal range of the MRP is 40À80 mmHg and, although a preoperative MRP of over 80 mmHg appeared to be related to more pain in the present study (P = 0.058), it was not an independent predictor of postoperative pain. This is supported by a recent study of SH [25] in which only 33.9% (41/121) of patients with postoperative severe pain (VAS > 3) had an increased anal resting pressure. It therefore seems that anal sphincter spasm is unlikely to be a frequent cause of severe pain after SH.…”
Section: Discussionsupporting
confidence: 62%
“… reported an opposite effect. Although male sex was a risk factor for pain after SH in the present study, few other studies on postoperative pain have included gender in the analysis . Age was not significantly associated with pain in the multivariate analysis, but it was significantly associated with pain in the univariate analysis and it may be that there are age‐related changes in physiological variables such as reduced rectal sensation which might explain this phenomenon .…”
Section: Discussioncontrasting
confidence: 52%
“…Metronidazole has been successfully used since 1998 for treating internal anal sphincter spasm [ 13 ], and its benefit after hemorrhoidectomy has been confirmed in a recent study [ 14 ]. Similarly, 0.2% glyceryl trinitrate has been successfully used to reduce both anal internal sphincter spasm and postoperative pain [ 14 , 15 , 33 36 ]. Patti et al reported the effectiveness of both the topical application of 0.2% glyceryl trinitrate ointment and botulinum injection over placebo in reducing postoperative pain at resting or during defecation and improving wound healing [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting our findings, it was described that sacral neuromodulation could be ineffective in treating pain after stapler procedures, while it could be useful for postoperative Impairment of daily life, taken of analgesic even opioids pain due to other procedures such as hysterectomy [11], suggesting a mechanical rather than a neuropathic alteration. Moreover, a possible therapeutic role was reported for glycerin trinitrate by the reduction of muscular tone [12,13], confirming the hypothesis of a muscular involvement.…”
Section: Discussionmentioning
confidence: 78%